2023
DOI: 10.1126/scitranslmed.abl7895
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Src reactivates pyroptosis to reverse chemoresistance in lung and pancreatic cancer models

Abstract: Pancreatic and lung cancers frequently develop resistance to chemotherapy-induced cell apoptosis during the treatment, indicating that targeting nonapoptotic-related pathways, such as pyroptosis, can be an alternative cancer treatment strategy. Pyroptosis is a gasdermin-driven lytic programmed cell death triggered by inflammatory caspases when initiated by canonical or noncanonical pathways that has been recently seen as a potential therapeutic target in cancer treatment. However, overcoming chemoresistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Pyroptosis-aroused immunological responses could convert immunosuppressive "cold" tumor microenvironment (TME) to immunogenic "hot" TME, which not only inhibits primary pancreatic cancer growth but also attacks the distant tumor (39). Pancreatic cancers frequently develop resistance to chemotherapy-induced cell apoptosis during the treatment, that targeting pyroptosis can be an alternative cancer treatment strategy (40). SEM results showed that knockdown of GALNT6 promoted the pyroptosis of PDAC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis-aroused immunological responses could convert immunosuppressive "cold" tumor microenvironment (TME) to immunogenic "hot" TME, which not only inhibits primary pancreatic cancer growth but also attacks the distant tumor (39). Pancreatic cancers frequently develop resistance to chemotherapy-induced cell apoptosis during the treatment, that targeting pyroptosis can be an alternative cancer treatment strategy (40). SEM results showed that knockdown of GALNT6 promoted the pyroptosis of PDAC cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, proteins of the Bcl-2 family can inhibit the apoptosis of lung cancer cells and promote the differentiation and function of OCs. Cytokines released during the apoptosis of lung cancer cells, such as TNF-α, TGF-β, and VEGF, can indirectly promote bone metastasis by fostering inflammation and angiogenesis within the tumor microenvironment ( 75 ). Additionally, the release of lactate and ATP post-apoptosis can upregulate the metabolic state of bone cells and increase acidification of the tumor microenvironment, indirectly facilitating bone resorption in the context of lung cancer bone metastasis ( 76 ).…”
Section: The Role Of the Bone Marrow Microenvironment In Lung Cancer ...mentioning
confidence: 99%
“…This effect is mediated through the upregulation of the sphingolipid metabolic enzyme ceramidase (ASAH2) expression, which is regulated by the STAT3 signaling pathway. The increased ceramidase expression results in a reduction of the metabolite ceramide concentration and subsequent suppression of reactive oxygen species (ROS) production, effectively blocking chemotherapy-induced canonical pyroptosis [ 70 ] .…”
Section: Applications Of 3d Culture Systems In Drug Resistance Researchmentioning
confidence: 99%